Patient characteristics associated with self-presentation, treatment delay and survival following primary percutaneous coronary intervention. Issue 3 (1st September 2014) - Austin, David; Yan, Andrew T; Spratt, James C; Kunadian, Vijay; Edwards, Richard J; Egred, Mohaned; Bagnall, Alan J
Abstract: Background: Delayed arrival to a primary percutaneous coronary intervention (PPCI)-capable hospital following ST-elevation myocardial infarction (STEMI) is associated with poorer outcome. The influence of patient characteristics on delayed presentation during STEMI is unknown. Methods and results: This was a retrospective observational study. Patients presenting for PPCI from March 2008 to November 2011 in the north of England (Northumbria, Tyne and Wear) were included. The outcomes were self-presentation to a non-PPCI-capable hospital, symptom to first medical contact (STFMC) time, total ischaemic time and mortality during follow-up. STEMI patients included numbered 2297; 619 (26.9%) patients self-presented to a non-PPCI-capable hospital. STFMC of >30 min and total ischaemic time of >180 min was present in 1521 (70.7%) and 999 (44.9%) cases, respectively. Self-presentation was the strongest predictor of prolonged total ischaemic time (odds ratio, OR (95% confidence interval, CI): 5.05 (3.99–6.39)). Married patients (OR 1.38 (1.10–1.74)) and patients living closest to an Emergency Room self-presented more commonly (driving time ( vs . ≤10 min) 11–20 min OR 0.66 (0.52–0.83), >20 minutes OR 0.46 (0.33–0.64). Unmarried females waited longest to call for help (OR vs . married males 1.89 (1.29–2.78) and experienced longer total ischaemic times (OR 1.51 (1.10–2.07)). Married patients had a borderline association with lower mortality (hazard ratio 0.75 (0.53–1.05), p =0.09). Conclusions: Unmarried female patients had the longest treatment delays. Married patients and those living closer to an Emergency Room self-present more frequently. Early and exclusive use of the ambulance service may reduce treatment delay and improve STEMI outcome.